Foreign Direct Investment, Regulations, and Growth - Busse, Matthias; Groizard, José Luis (World Bank, Washington, DC, 2012)
This paper explores the linkage between income growth rates and foreign direct investment (FDI) inflows. So far the evidence is rather mixed, as no robust relationship between FDI and income growth has been established. The authors argue that countries need a sound business environment in the form of good government regulations to be able to benefit from FDI. Using a comprehensive data set for regulations, they test this hypothesis and find evidence that excessive regulations restrict growth through FDI only in the most regulated economies. This result holds true for different specifications of the econometric model, including instrumental variable regressions.